Pre-hospital transfusion of packed red blood cells in 147 patients from a UK helicopter emergency medical service. Issue 1 (December 2017) - Lyon, Richard; de Sausmarez, Eleanor; McWhirter, Emily; Wareham, Gary; Nelson, Magnus; Matthies, Ashley; Hudson, Anthony; Curtis, Leigh; Russell, Malcolm
Abstract Background Early transfusion of packed red blood cells (PRBC) has been associated with improved survival in patients with haemorrhagic shock. This study aims to describe the characteristics of patients receiving pre-hospital blood transfusion and evaluate their subsequent need for in-hospital transfusion and surgery. Methods The decision to administer a pre-hospital PRBC transfusion was based on clinical judgment. All patients transfused pre-hospital PRBC between February 2013 and December 2014 were included. Pre-hospital and in-hospital records were retrospectively reviewed. Results One hundred forty-seven patients were included. 142 patients had traumatic injuries and 5 patients had haemorrhagic shock from a medical origin. Median Injury Severity Score was 30. 90% of patients receiving PRBC had an ISS of >15. Patients received a mean of 2.4(±1.1) units of PRBC in the pre-hospital phase. Median time from initial emergency call to hospital arrival was 114 min (IQR 103–140). There was significant improvement in systolic (p  < 0.001), diastolic (p  < 0.001) and mean arterial pressures (p  < 0.001) with PRBC transfusion but there was no difference in HR (p  = 0.961). Patients received PRBC significantly faster in the field than waiting until hospital arrival. At the receiving hospital 57% required an urgent surgical or interventional radiology procedure. At hospital arrival, patients had a mean lactate of 5.4(±4.4) mmol/L, pH of 6.9(±1.3) and base deficit of −8.1(±6.7). Mean initial serum adjusted calcium was 2.26(±0.29) mmol/L. 89% received further blood products in hospital. No transfusion complications or significant incidents occurred and 100% traceability was achieved. Discussion Pre-hospital transfusion of packed red cells has the potential to improvde outcome for trauma patients with major haemorrhage. The pre-hospital time for trauma patients can be several hours, suggesting transfusion needs to start in the pre-hospital phase. Hospital transfusion research suggests a 1:1 ratio of packed red blood cells to plasma improves outcome and further research into pre-hospital adoption of this strategy is needed. Conclusion Pre-hospital PRBC transfusion significantly reduces the time to transfusion for major trauma patients with suspected major haemorrhage. The majority of patients receiving pre-hospital PRBC were severely injured and required further transfusion in hospital. Further research is warranted to determine which patients are most likely to have outcome benefit from pre-hospital blood products and what triggers should be used for pre-hospital transfusion.